Mediterranean diet adherence and tirzepatide: real-world evidence on adiposity indices and insulin resistance beyond weight loss - Paternò, Valentina; Geraci, Giulio; Piticchio, Tommaso; Le Moli, Rosario; Burgio, Stefano; Costanzo, Gabriele; Sambataro, Gianluca; Baratta, Roberto; Barbagallo, Federica; Pallotti, Francesco (Frontiers in Endocrinology, 2026)
IntroductionTirzepatide, a dual GIP/GLP-1 receptor agonist, is highly effective in reducing body weight and improving glucometabolic outcomes. However, most clinical trials have overlooked the role of diet quality, leaving unclear whether lifestyle factors may modulate pharmacological benefits. The Mediterranean diet, assessed through the validated PREDIMED score, has proven effects on visceral adiposity and metabolic health and may act synergistically with novel incretin therapies.Materials and methodsWe enrolled 53 patients with overweight/obesity eligible for tirzepatide (BMI ≥ 30 kg/m2 or BMI ≥ 27 kg/m2 with comorbidities). Participants were clinically assessed at baseline (T0) and after a median of 3 months (T1) of treatment (2.5 mg/week for 1 month, then 5.0 mg/week). All patients received personalized recommendations for a Mediterranean dietary plan. Anthropometric measures, adiposity indices (BMI, WC, WtHR, BRI, ABSI, VAI), biochemical parameters, and PREDIMED scores were collected at both visits. Correlations and generalized linear models were applied to explore the relationship between dietary adherence and changes in adiposity indices.ResultsAfter three months, patients showed significant reductions in weight, BMI, WC, WtHR, BRI, and VAI (all p < 0.05), while ABSI remained unchanged. The glucometabolic profile improved consistently, with declines in fasting glucose, insulin, HbA1c, and triglycerides, alongside higher HDL-c. PREDIMED scores increased substantially (mean +3.2 points, p < 0.001). Higher adherence to the Mediterranean diet was associated with lower insulin levels, improved HOMA index, and greater reductions in VAI, even after adjusting for age, gender, and BMI.ConclusionThis real-world study confirms the efficacy of tirzepatide on adiposity and metabolic markers and provides exploratory evidence that adherence to a Mediterranean diet enhances its impact on visceral adiposity. The combination of pharmacological therapy and diet quality may offer additive benefits, and the integration of both PREDIMED and VAI in future studies could support more comprehensive strategies for cardiometabolic risk stratification and obesity care.